Aerobic fitness and obesity: relationship to cerebral white matter integrity in the brain of active and sedentary older adults. Issue 15 (17th June 2010) - Marks, BL; Katz, LM; Styner, M; Smith, JK
Abstract : Objective: Aerobic fitness (VO2 peak) and obesity risk (OR) may impact brain health. This study examined hemispheric and segment specific relationships between VO2 peak, OR and cerebral white-matter (CWM) integrity in the cingulum brain region in healthy older adults. Methods: Fifteen subjects (66±6 years) completed VO2 peak testing and MRI of the brain. OR was determined via body mass index (BMI) and abdominal girth. MRI analysis was performed with a structural 3D T1 MP-Rage and diffusion tensor imaging technique (DTI, 21 directions, repeated four times) on a 3.0 T MR imaging unit. CWM integrity indices, fractional anisotropy (FA) and mean diffusivity (MD), were computed from the tensors. The anterior, middle and posterior cingulum segments were analysed on both sides of the brain. Partial correlations (age and gender controlled) and standard multiple regressions were used to determine significant associations and unique contributions to CWM integrity. Results: VO2 peak was moderately related to FA in the left middle cingulum segment (r partial=0.573, p=0.041) and explained 28.5% of FA's total variance (p=0.10). Abdominal girth (r partial=−0.764, p=0.002) and BMI (r partial=−0.690, p=0.009) were inversely related to FA in the right posterior cingulum (RPC) segment. Abdominal girth and BMI uniquely explained 53.9% of FA's total variance (p=0.012) and 43.9% (p=0.040), respectively, in the RPC. Conclusion: Higher aerobic fitness and lower obesity risk are related to greater CWM integrity but not in the same cingulum segments.